2017
DOI: 10.1038/srep45489
|View full text |Cite
|
Sign up to set email alerts
|

A Gate Hinge Controls the Epithelial Calcium Channel TRPV5

Abstract: TRPV5 is unique within the large TRP channel family for displaying a high Ca2+ selectivity together with Ca2+-dependent inactivation. Our study aims to uncover novel insights into channel gating through in-depth structure-function analysis. We identify an exceptional tryptophan (W583) at the terminus of the intracellular pore that is unique for TRPV5 (and TRPV6). A combination of site-directed mutagenesis, biochemical and electrophysiological analysis, together with homology modeling, demonstrates that W583 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
5
20
0
Order By: Relevance
“…5c,d). Our structural observation is consistent with a recent mutagenesis study 7 that suggested a similar gating mechanism for the TRPV5 channel and implicated His582 in this mechanism.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…5c,d). Our structural observation is consistent with a recent mutagenesis study 7 that suggested a similar gating mechanism for the TRPV5 channel and implicated His582 in this mechanism.…”
Section: Resultssupporting
confidence: 92%
“…6). Finally, consistent with the recent mutagenesis and structural studies 7 , we determined that in addition to the Met578, the rotation of the Phe574 and possibly His582 into the pore may further block Ca 2+ ion flow through TRPV5 (Fig. 6).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To explore the influence of W583, we determined a structure of full length TRPV5 with a W583A point mutation in nanodisc to 2.85 Å resolution. Consistent with previously reported 'gain-of-function' phenotype for the W583 mutants (18), the lower gate of the TRPV5 W583A structure has an open conformation (Supplemental Fig. 3).…”
Section: Ion Permeation Pathwaysupporting
confidence: 89%
“…2e). Indeed, W583 is conserved in TRPV6 and TRPV5 channels and is involved in regulation of calcium uptake, as evidenced by mutation W583A in TRPV5, which induces cell death due to increased calcium influx 19 . The density at the S6 helices bundle crossing, which was not observed in the pore of the closed-state rTRPV6 10,11 , most likely represents another permeant ion bound in the open pore of hTRPV6.…”
mentioning
confidence: 99%